Cognitive clamping geometries for monitoring elastic deformation in forming machines and processes. Issue 1 (2021) - Kurth, Robin; Bergmann, Markus; Tehel, Robert; Dix, Martin; Putz, Matthias
Abstract: In the context of inline monitoring and controlling of forming processes, the distribution of acting forces on tool and forming machine causing elastic deformation of the clamping surfaces provides fundamental information on the resulting part quality whereas the inline detection is still challenging. This paper presents a novel method using the T-slot geometry as a cognitive area for inline analyzing of the elastic deformation of the tool-clamping surfaces. Using a newly developed sensor device, the elastic deformation state of the T-slot geometry under process forces is detected by strain measuring of a deformation body mounted inside the T-slot. The functionality principle of the sensor device and measuring method for process monitoring are demonstrated by simulation and experiments, demonstrating the potential for process control.